Toward A Structured, Tri-Domain Model Of Companioning In Christian Formation By Pastoral Agents In A Congregational Setting: A Preliminary Report On An International Research Project. (June 2018) - Pembroke, Neil; Coyle, Suzanne; Gear, Janet; Gubi, Peter; Kelly, Ewan; Louw, Daniel; McMillan, Lex; Niven, Alan; Thierfelder, Constanze; Schmidt, William; van den Berg, Jan-Albert
A preliminary report is presented by an international project team working on developing a model for a structured and holistic approach to companioning parishioners in the journey of formation in the Christian life. A holistic model involves working in three domains: positive psychology, spirituality, and personal and social ethics. Structure is provided by utilizing four self-assessment instruments to inform the work the pastor and the parishioner do together.